Analisa Rancangan Kode Sandi Keypad pada Smart Lock Door System Berbasis IOT - Al-Rasyid, Johansyah; Nawawi, M.; Pratiwi, Chitra Putri (Jurnal Teknologi Informasi dan Pendidikan, 2023)
Along with the rampant crime lately, people are always wary of the valuable assets they have. This study discusses the security system, especially at the door of a building. The automatic door security system uses a solenoid lock door with a keypad as input and a vibration sensor as a detector if there is vibration. When the passcode input via the keypad is high or true, the microcontroller in the form of Arduino Uno will give an order to the relay and will activate the solenoid, so the door will open automatically and send a message via telegram. The results of this study indicate that the automatic door system using the keypad works well. This is evidenced by Arduino Uno, which gets input from the keypad, goes according to orders with the password code that has been programmed before, thereby activating the solenoid which receives input from the relay that the entered passcode is correct, and the door will open automatically by giving a notification. go to telegram. As well as a vibration sensor that detects if there is vibration at the door going well.